PENGEMBANGAN MODUL IPA TERPADU YANG DILENGKAPI MODEL PEMBELAJARAN SCAFFOLDING PADA MATERI PENCEMARAN LINGKUNGAN UNTUK SISWA KELAS VII SMP/MTS - Arpela Rahayu; Arista Ratih; Rodiantifitri Nengsih (Pendidikan Biologi STKIP YPM Bangko, 2021)
This research is motivated by the lack of teaching materials used and the lack of attractive teaching materials used and not yet combined with attractive colors. To overcome this problem, it is necessary to develop supporting teaching materials, namely in the form of learning modules equipped with scaffolding on environmental pollution material. This study aims to describe the process of developing an Integrated Science learning module equipped with Scaffolding on environmental pollution material for grade VII SMP / MTS students, to produce an Integrated Science module equipped with Scaffolding on environmental pollution material for class VII SMP / MTS which is valid and practical. This type of research is a type of development research that uses a 4-D model which includes the stages of define (define), Design (Design), Develop (Development) and Desseminate (deployment). The subject of this study consisted of 6 validators. For practicality it was carried out by 2 teachers 31 students of class VII SMP / MTS. Sources of data from the results of this study are the results of the validity and practicality of the learning module, then this data is analyzed by descriptive analysis. Based on the results of this study, a product in the form of an integrated science learning module equipped with valid and practical scaffolding was produced. The resulting learning module was declared very valid by the validator both from the aspects of the feasibility of content, language, presentation and graphics with an achievement of a value of 96%. The resulting learning module was also stated to be very practical by the teacher both in terms of ease of use, learning time and aspects of attractiveness with an average score of 3.78. Based on the data analysis obtained, it can be concluded that the Integrated Science learning module which is equipped with Scaffolding on environmental pollution material for grade VII SMP / MTS students has been declared very valid and very practical.